Perception of Women regarding Respectful Maternity Care during Childbirth in Maternity Hospital, Kathmandu - Kisi, Durgeshori; Manandhar, Maiya Shobha; Acharya, Sharada (Journal of Karnali Academy of Health Sciences, 2024)
Background: Disrespectful and abusive care has been recognized as one of the barriers to seek timely maternity health services. One of the crucial ways to increase institutional deliveries is providing respectful maternity care. Women will be motivated to facility-based delivery only when they get respectful care during childbirth. Thus, the study aimed to identify perception of women regarding Respectful Maternity Care (RMC) during childbirth.Method: A descriptive cross-sectional design was applied among 196 women in Postnatal ward of Paropakar Maternity and Women’s hospital, Kathmandu. Non probability purposive sampling technique was adopted to select the study area. Study participants were selected by using simple random sampling technique. Face to face interview was done by using standard RMC tool. Descriptive and inferential statistics were used to analyze the data.Results: In total, 92.9% women reported that they have experienced overall RMC services. Though majority of women experienced RMC services on different domain, they also experienced disrespectful care in various forms such as not cared with kind approach (15.3%); being shouted (4.1%); keep waiting for long time (23.5%); delay provision of services (17.9%) and being insulted (13.8%). There was association between overall perception on RMC and education (p=0.049).Conclusion: Most of the women reported they have experienced RMC services on different domains. Some women experience disrespectful care in various forms. Therefore, woman-centered care should be provided in a respectful and non-abusive manner through capacitating institutional structure and updating professional by ongoing in-service and academic training.